Metagenomic Analysis of Uterine Microbiota in Postpartum Normal and Endometritic Water Buffaloes (Bubalus bubalis) - Onnureddy, K.; Vengalrao, Y.; Mohanty, T.K.; Singh, Dheer (Journal of Buffalo Science, 2013)
In Indian subcontinent the water buffalo (Bubalus bubalis) is one of the important livestock animals. As in cows, postpartum infection like endometritis in dairy buffaloes is major cause for the economic loss in the dairy industries. Till date, there is no study regarding metagenomic analysis of bacterial population of postpartum endometritic buffaloes. The purpose of this study was to identify and compare the uterine bacterial composition in normal and endometritic postpartum buffaloes using 16S rDNA cloning, which was a type of culture-independent methods. A total of 151 cloned plasmids for 16S rDNA from both normal and endometritic uterine samples were sequenced. Cloning library of 16S rDNA revealed clear cut difference between bacterial populations of normal and endometritic postpartum buffaloes. Cloned sequences were assigned to five major groups and one uncultured group. The five major groups include- Bacteroidetes, Firmicutes, Fusobacteria, Proteobacteria, and Tenericutes. Major cloned sequences from normal status endometrium were affiliated to phylum Proteobacteria, and most of the sequences showed high degree of similarity with bacteria Haemophilus felis. Most of the sequences from cloned library of endometritic status samples were affiliated to phylum Proteobacteria and Tenericutes. The most prevalent bacteria found in endometritic samples were Psychrobacter sp. PRwf-1, Psychrobacter pulmonis, Ureaplasma diversum strain T95 and Ureaplasma diversum strain A417. A major number of cloned sequences from both normal and endometritic samples were assigned to uncultured group. The present data showed bacterial population of postpartum normal and endometritic buffaloes and also described the presence of various types microbiota in uterine samples.